Shift-invariant measures on infinite-dimensional spaces: Integrable functions and random walks - V.Zh. Sakbaev; D.V. Zavadsky (Учёные записки Казанского университета: Серия Физико-математические науки)
Averaging of random shift operators on a space of the square integrable by shift-invariant measure complex-valued functions on linear topological spaces has been studied. The case of the l∞ space has been considered as an example.